Fundamentals of biofuel production processes - Das, Debabrata, 1953-; Varanasi, Jhansi L. (Boca Raton : Taylor & Francis, CRC Press, 2019)
Focusing on fundamentals of biofuel production from renewable energy sources and biohydrogen production, this book offers a complete understanding of the bioconversion processes. Each chapter begins with a fundamental explanation for general readers and ends with in-depth scientific details suitable for expert readers. It discusses different types of production technologies covering basic concepts, production strategies, commercial usage, and advances.
OCLC-licensed vendor bibliographic record.
Keywords: Biomass energy; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; TECHNOLOGY / Engineering / Chemical & Biochemical; SCIENCE / Biotechnology